Association between dietary protein intake and risk of chronic kidney disease: a systematic review and meta-analysis - Cheng, Yu; Zheng, Guanghao; Song, Zhen; Zhang, Gan; Rao, Xuepeng; Zeng, Tao (Frontiers in Nutrition, 2024)
Objective: There is suggestive data indicating a correlation among dietary protein intake and the progression of chronic kidney disease (CKD). Nonetheless, the exact associations between dietary protein intake and the incidence of CKD have remained uncertain. We performed the first meta-analysis to explore the correlation among total protein, plant protein, animal protein intake and CKD risk.The study conformed the PRISMA statement guidelines. We comprehensively searched PubMed, Web of Science, and Embase until to December 2023. The retrieved studies underwent rigorous evaluation for eligibility, and relevant data were meticulously extracted. The Newcastle-Ottawa Scale (NOS) tool was applied to evaluate the risk of bias. Subsequently, relevant data were extracted and pooled to evaluate the relations among dietary protein intake and CKD incidence.Results: Totally, 6191 articles were identified, six studies were eligible. A total of 148,051 participants with 8746 CKD cases were included. All studies had a low overall risk of bias. Higher total, plant and animal protein intake were all correlated with decreased CKD incidence, pooled risk ratios (RRs) and 95% confidence intervals (CIs) were as follows: (RR=0.82, 95% CI=0.71-0.94, P = 0.005; I 2 = 38%, P = 0.17);(RR = 0.77, 95% CI = 0.61-0.97, P = 0.03; I 2 = 77%, P = 0.001); (RR = 0.86, 95% CI = 0.76-0.97, P = 0.02; I 2 = 0%, P = 0.59), respectively. For fish and seafood within animal protein: RR=0.84, 95% CI=0.74-0.94. Subgroup analysis showed that geographical region, sample size, follow-up time, not assessing protein by food frequency questionnaire, using %energy as the measurement index, not adjusting for several covariates may be the sources of heterogeneity for plant protein. A significant non-linear relation among plant protein and incident CKD was observed by dose-response analysis.The data showed a lower CKD risk significantly associated higher-level dietary total, plant or animal protein (especially for fish and seafood) intake. Further prospective studies demonstrated the correlations of precise sources, intake and duration of dietary protein and incident CKD are warranted.